Primary leiomyosarcoma of the mesentery in two sisters: clinical and molecular characteristics - Koczkowska, Magdalena; Lipska, Beata S.; Grzeszewska, Joanna; Limon, Janusz; Biernat, Wojciech; Jassem, Jacek (Polish Journal of Pathology, 2013)
Mesenteric leiomyosarcoma (LMS) is a very rare malignancy whose familiar occurrence has not yet been reported. We present two sisters who developed intestinal LMS. Pathological analysis of the tumor samples, including evaluation of smooth muscle actin+, desmin+, Myf4–, DOG-1–, S100–, CD34– and CD117– confirmed LMS diagnosis. Molecular analysis of the lesions, both primary tumors and a liver metastasis, revealed several genomic imbalances, with recurrent chromosomal aberration: interstitial gain at chromosome 17p11.2-13.1 with the minimal overlapping region of 9.2 Mb. Our study provides further evidence for the significant role of the genes located in this region in the early stage of carcinogenesis.